Application of computer on Pharmacogenomics - Amanat, Muhammed; Singh, Randhir (Bangladesh Journal of Medical Science, 2024)
Background Pharmacogenomics is an emerging field that explores the relationship between a person’s genetic makeup and their response to drugs. Objectives: Computer applications have been instrumental in advancing pharmacogenomics research and facilitating personalized medicine. In this abstract, we review some of the key computer applications used in pharmacogenomics research, including bioinformatics tools for analyzing genetic data, machine learning algorithms for predicting drug response, and clinical decision support systems for guiding drug selection and dosing. We also highlight the challenges and opportunities in the field of pharmacogenomics, including the need for large-scale, multi-omics datasets, and the importance of developing robust and interpretable machine learning models. Overall, computer applications have played a critical role in enabling pharmacogenomics research and have the potential to revolutionize the practice of medicine by facilitating the development of more personalized and effective drug therapies. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 300-308